2021
DOI: 10.3390/polym13162797
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances in Design and Preparation of Polymer-Based Thermal Management Material

Abstract: The boosting of consumer electronics and 5G technology cause the continuous increment of the power density of electronic devices and lead to inevitable overheating problems, which reduces the operation efficiency and shortens the service life of electronic devices. Therefore, it is the primary task and a prerequisite to explore innovative material for meeting the requirement of high heat dissipation performance. In comparison with traditional thermal management material (e.g., ceramics and metals), the polymer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 170 publications
0
16
0
Order By: Relevance
“…Among these, ceramics have shown electrical insulation properties. Therefore, the polymer‐based composite materials including ceramics can maintain insulation performance to some extent 6,7 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among these, ceramics have shown electrical insulation properties. Therefore, the polymer‐based composite materials including ceramics can maintain insulation performance to some extent 6,7 …”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the polymer-based composite materials including ceramics can maintain insulation performance to some extent. 6,7 Many types of ceramics have been used to enhance the k of polymer-based composites. Hexagonal boron nitride (hBN) is one of the most common ceramic fillers used to increase k. [8][9][10] Hexagonal boron nitride has a large amount of anisotropic k and the k in the in-plane direction (a-axis, [100]) has reached values as high as 600 W/(m K).…”
Section: Introductionmentioning
confidence: 99%
“…The overconsumption of energy is becoming a critical issue, based on engineering, environmental, and economic challenges in modern industries [ 1 , 2 , 3 ]. Pursuing a novel material with high performance and energy efficiency is a forefront research topic in terms of industrial applications [ 4 , 5 , 6 , 7 ]. Aerogel, as an impressive commercial energy material, plays a crucial role in the thermal insulation field due to its high strength and low density, which can be subdivided into inorganic and organic aerogels.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, the introduction of fillers with high thermal conductivity into polymer matrix to prepare polymer composites has attracted a considerable amount of attention, and it has been confirmed that this is an effective way to enhance the thermal conductive property of polymer matrices in academia and industry [7,8]. Traditional thermal conductive fillers used to prepare high thermal conductivity polymer composites include metal fillers (Al and Cu), carbon-based materials (graphene and carbon nanotubes) and ceramic fillers (AlN, BN, Al2O3 and SiC) [9][10][11]. Unfortunately, the addition of metal fillers or carbon-based fillers tends to damage the insulation property of the material to a certain extent, while ceramic fillers show unquestionable advantages due to their high thermal conductivity and electrical resistivity [12].…”
Section: Introductionmentioning
confidence: 99%